A survey of the pyrabactin resistance-like abscisic acid receptor gene family in poplar. (3rd August 2017) - Yu, Jingling; Li, Hejuan; Peng, Yajing; Yang, Lei; Zhao, Fugeng; Luan, Sheng; Lan, Wenzhi
ABSTRACT: The conserved PYR/PYL/RCAR family acts as abscisic acid (ABA) receptors for land plants to adapt to terrestrial environments. Our recent study reported that the exogenous overexpression of poplar PtPYRL1 and PtPYRL5, the PYR/PYL/RCAR orthologs, promoted the sensitivity of transgenic Arabidopsis to ABA responses. Here, we surveyed the PtPYRL family in poplar, and revealed that although the sequence and structure are relatively conserved among these receptors, PtPYRL members have differential expression patterns and the sensitivity to ABA or drought treatment, suggesting that PtPYRLs might be good candidates to a future biotechnological use to enhance poplar resistance to water-stress environments.